First Case of Sporadic Protein S Deficiency due to a Novel Candidate Mutation, Ala 484 → Pro, in the Protein S Active Gene (PROSl) - Borgel, D; Jude, B; Alach, M; Gandrille, S (Thrombosis and Haemostasis, 1996)
In a series of 16 propositi with symptomatic protein S deficiency and a protein S gene mutation, we identified a sporadic case of a novel mutation that probably affects gene expression. The mutation, a G to C transversion leading to the substitution of Ala 484 by Pro, was not found in the protein S gene of the patient’s parents. Transmission of the paternal and maternal protein S alleles was apparently normal, on the basis of the frequent polymorphism in exon XV. We also checked the transmission of chromosomal material by analysing protein C gene polymorphisms, Β-globin gene frameworks and four variable number of tandem repeats (VNTRs). By combining the results of these analyses, we were able to rule out nonpaternity and to confirm the de novo nature of the mutation.